Strategi Komunikasi SMPN 1 Garut dalam Mencegah Kasus Bullying di Sekolah - Neneng Eka Purwaningsih; Ummu Salamah; Yandi Hermawandi (LPPM Institut Pendidikan Nusantara Global, 2025)
Bullying in schools is a serious issue that can disrupt students’ psychological and academic development. Preventing bullying requires effective communication strategies so that anti-bullying messages can be well-received and internalized by students. This study aims to analyze the communication strategies of SMPN 1 Garut in preventing bullying cases in the school environment. The study focuses on four main aspects: understanding the audience, crafting messages, determining methods, and selecting media. The research method used is descriptive qualitative, with data collection techniques including observation, in-depth interviews, literature study, and documentation. Data analysis was carried out using the communication strategy theory approach by Anwar Arifin. The results of the study indicate that SMPN 1 Garut has implemented effective communication strategies. In understanding the audience, the school conducts behavioral observations, receives reports from counseling teachers, and monitors students’ activities on social media. Message formulation is carried out in a persuasive and educational manner, using storytelling and real-life examples. The methods employed involve a combination of informative, persuasive, redundancy, canalizing, and interactive approaches. The media used include print media, electronic media, and social media platforms such as Instagram and TikTok. This approach has proven effective in raising students’ awareness about the negative impact of bullying and in creating a safe, comfortable, and conducive school environment for all members of the school community.